2022
DOI: 10.1002/jmv.27955
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological features and sociodemographic factors associated with mumps in mainland China from 2004 to 2018

Abstract: Mumps is an acute infectious disease that spreads widely around the world. The aim of this study was to investigate the epidemiological features and sociodemographic factors associated with mumps in mainland China from 2004 to 2018. Incidence data for mumps during the period 2004-2018 were collected from the Public Health Sciences Data Center of China. Joinpoint regression analysis was performed to explore the trends of mumps. Space-time clustering analysis was conducted to spatial and temporal aggregation are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…That is to say, the higher the level of economic development in the local and surrounding areas, the higher the local mumps incidence. Currently, only the study by Fu et al has found an inverse relationship between GDP and mumps using linear regression, which is consistent with the results of our study [ 16 ]. There is no doubt that the level of GDP determines the amount of money spent on public health, which is conducive to disease control.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…That is to say, the higher the level of economic development in the local and surrounding areas, the higher the local mumps incidence. Currently, only the study by Fu et al has found an inverse relationship between GDP and mumps using linear regression, which is consistent with the results of our study [ 16 ]. There is no doubt that the level of GDP determines the amount of money spent on public health, which is conducive to disease control.…”
Section: Discussionsupporting
confidence: 93%
“…During the study period, it was clear that the morbidity of mumps fluctuated and increased from 13.70/100,000 in 2014 to 18.56/100,000 in 2018, consistent with a previous study [ 16 ]. This may be related to the epidemic periodicity of mumps and the attenuation of antibodies in susceptible populations.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, some mumps epidemics occurring in Chinese schools showed that more boys than girls were affected. 16 A national study in Finland, a country in which mumps has been eliminated, found no difference in antibody levels between boys and girls during the first few years after second-dose MMR vaccination; however, antibody levels were significantly lower in boys than in girls 8 years after MMR. 24 Several reports of mumps outbreaks in schools in the United States indicated that more girls than boys were infected with the mumps virus.…”
Section: Discussionmentioning
confidence: 99%
“… 15 To improve immunity against the mumps virus and reduce the incidence of mumps, a second dose of MuCV was recommended for children in several provinces of China, with the number of cases of mumps decreasing dramatically due to earlier administration of the second dose of MMR to children aged 4–6 years. 16 Beginning in July 2020, the Chinese government implemented a two-dose MMR immunization schedule, at ages 8 and 18 months; however, data on the effect of the two-dose MMR regimen on mumps incidence remained limited. 17–19 …”
Section: Introductionmentioning
confidence: 99%